2017
DOI: 10.1002/aic.15934
|View full text |Cite
|
Sign up to set email alerts
|

On the use of a powder rheometer to characterize the powder flowability at low consolidation with torque resistances

Abstract: The Anton Paar Powder Cell was used to measure the torque necessary to rotate an impeller in beds of glass beads, sand and alumina powders aerated between no aeration to the minimum for fluidization. Measured torque values depend on the material tested, on the air flow rate applied, on the impeller depth and on the height of the impeller blade. The effect of the impeller depth is linear for low impeller depth and is less than linear at high depth values. A model was developed for the interpretation of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The cell containing the powder is made of a glass cylinder with a porous bottom plate, and the unit is equipped with impellers of different shapes and wall conditions. Salehi et al (2017b) used an APPC to study the effects of the impeller depth and the aeration rate on the torque acting on a flat blade impeller in samples of free-flowing powders, namely glass beads, alumina and sieved silica sand, up to the minimum fluidisation (0 < FI < 1). The dependency of T on the air velocity, the bed height and the impeller depth confirm the observations of Bruni et al (2005;2007).…”
Section: R8mentioning
confidence: 99%
“…The cell containing the powder is made of a glass cylinder with a porous bottom plate, and the unit is equipped with impellers of different shapes and wall conditions. Salehi et al (2017b) used an APPC to study the effects of the impeller depth and the aeration rate on the torque acting on a flat blade impeller in samples of free-flowing powders, namely glass beads, alumina and sieved silica sand, up to the minimum fluidisation (0 < FI < 1). The dependency of T on the air velocity, the bed height and the impeller depth confirm the observations of Bruni et al (2005;2007).…”
Section: R8mentioning
confidence: 99%
“…The powder bed can also be conditioned prior to torque measurement to remove any residual vertical friction due to insertion of the impeller in the bed. Recently, Salehi et al (2017), evaluated the Anton Paar powder cell for characterising flowability at low stresses using glass beads, sand and alumina powder. They reported that the minimum torque necessary to rotate an impeller in a powder bed depends on material properties, air flow rate, impeller depth and shape of the impeller.…”
Section: Powder Cell Of the Anton Paar Modular Compact Rheometermentioning
confidence: 99%
“…By introducing the permeating air, the powder flow, which is initially in the quasistatic state, could transform into the intermediate or even dynamic state, where the bulk friction coefficient is shown to increase almost linearly with the inertial number. Bruni et al (2007Bruni et al ( , 2005 and Tomasetta et al (2012) used a mechanically stirred fluid-bed rheometer to study the rheology of aerated and fluidised powders, which was followed by Salehi et al (2017Salehi et al ( , 2018. To keep the bed in quasi-static state, the rotational speed of the impeller and gas superficial velocity were chosen to have low values.…”
Section: Effect Of Shear Strain Rate and Medium Fluid Dragmentioning
confidence: 99%
“…Particulate materials should ideally retain their desired flow properties during processing, handling and storage as well as through the distribution chain to the final consumer [1]. These types of reduction in the handling behaviour of particulate materials can lead to huge costs being imposed on industries [2]. Such costs justify the need for developing a tester for measuring as well as means for predicting caking at industrial scales.…”
Section: Accepted Manuscriptmentioning
confidence: 99%